Ghost crystallography - Zhang, Minghui; Wei, Huazhe; Liu, Xianlong; Hoenders, Bernhard J.; Guo, Lina; Cai, Yangjian (Frontiers in Physics, 2022)
In [Opt. Lett. 38, 4023-4025 (2013)] the author predicted that the low coherent X-ray is hard to provide a high-resolution diffraction pattern from an object with a spatially periodic structure. This would severely restrict X-ray crystallography and its similar techniques. In this letter, we indicate that the Ghost diffraction technic takes advantage of the low coherence and may thus break through the bottleneck. Analytical formulae for calculating ghost diffraction patterns diffracted by the periodic structured media under any coherent state are derived.